Multi-Component Syntheses of Spiro[furan-2,3′-indoline]-3-carboxylate Derivatives Using Ionic Liquid Catalysts - Khalaj, Mehdi; Zarandi, Maryam; Samadi Kazemi, Malihe; Musavi, Seyed Mahmoud; Hohnsen, Johannes; Klein, Axel (Molecules (Basel, Switzerland), 2024)
Two previously described Brønsted acidic ionic liquids, 3,3′-(1,6-hexanediyl)bis(1-methyl)-1H-imidazolium hydrogen sulfate (Cat1) and 1,1′-(1,6-hexanediyl)bis(pyridinium) hydrogen sulfate (Cat2), were used as catalysts for the preparation of spiro[furan-2,3′-indoline]-3-carboxylate derivatives via a three-component reaction of anilines, isatins (N-alkyl-indoline-2,3-diones), and diethyl acetylenedicarboxylate, in high yields. The use of ultrasonic (US) irradiation led to the targeted products (1a–15a) in high yields ranging from 80% to 98%. Under the same conditions, the use of sulfuric acid and acetic acid as a Brønstedt catalyst did not yield the desired benchmark product 1a.